The Influence of English Medium of Instruction on Students’ Academic Performance in Technical Institutions in Tanzania: A Case of Arusha Technical College - Ngaai, Victor (Papanda Publisher, 2024)
The main objective of this study was to explore the influence of English as a medium of instruction on students’ academic Performance at Arusha Technical College in Tanzania. This came after observing how the two languages: Kiswahili and English act as medium of instruction from lower to the higher levels of education respectively. English, as a second language in Tanzania, and a medium of instruction in higher learning institutions has shown discrepancies in students’ academic performance. Therefore, the study focused mainly on three specific objectives: to explore the use of English as a medium of instruction in terms of teachers’/students’ competency and confidence of students at Arusha Technical College, to describe the student’s academic performance in terms of proficiency in EMI, continuous assessment, and semester examination of students at Arusha Technical College, and to determine the relationship between the use of English as a Medium of instruction and the student’s academic performance in Tanzania. The study employed a quantitative research method specifically using descriptive and correlational research design. The secondary data were collected through a literature review; while the primary data were obtained through a self-constructed questionnaire. Questionnaire data were analyzed through the use of the Statistical Package for Social Sciences version 24 (SPSS). The study used a sample size of 100 respondents from Arusha Technical College where the English language is used as a medium of instruction. The results of the study revealed that most students had sufficient English language mastery due to the background of their previous education level. This fact led to the understanding and success in speaking and writing good English. Further, the findings showed that the lecturers used code-switching and translation strategies to enable students to understand the lessons. The study recommends a need for further research to be conducted on other institutions of higher learning to make rational decisions about usefulness of the language of instruction.